The Taj: an architectural marvel of an epitome of love? - Islam, Arshad (INSI Publications, 2013)
On Saturday 7th July 2007, the New Seven Wonders Foundation, Switzerland, in its new ranking, again declared the Taj Mahal to be one of the Seven Wonders of the World. The Taj Mahal is not just an architectural feat and an icon of luminous splendour, but an epitome of enormous love as well. The Mughal Emperor Shahjahan (1592-1666) built the Taj Mahal, the fabulous mausoleum(rauza), in memory of his beloved queen Mumtaz Mahal (1593-1631). There is perhaps no better and grander monument built in the history of human civilization dedicated to love. The contemporary Mughal sources refer to this marvel as rauza-i-munavvara(‘the illumined tomb’); the Taj Mahal of Agra was originally called Taj Bibi-ka-Rauza.It is believed that the name ‘Taj Mahal’has been derived from the name of Mumtaz Mahal (‘Crown Palace’). The pristine purity of the white marble, the exquisite ornamentation, use of precious gemstones and its picturesque location all make Taj Mahal a marvel of art. Standing majestically at the southern bank on the River Yamuna, it is synonymous with love and beauty. This paper highlights the architectural design and beauty of the Taj, and Shahjahan’s dedicated love for his beloved wife that led to its construction